2010
DOI: 10.1074/jbc.m109.072504
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pre-replicative Complex Assembly

Abstract: The pre-replicative complex (pre-RC) is formed at all potential origins of replication through the action of the origin recognition complex (ORC), Cdc6, Cdt1, and the Mcm2-7 complex. The end result of pre-RC formation is the loading of the Mcm2-7 replicative helicase onto origin DNA. We examined pre-RC formation in vitro and found that it proceeds through separable binding events. Origin-bound ORC recruits Cdc6, and this ternary complex then promotes helicase loading in the presence of a pre-formed Mcm2-7-Cdt1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 29 publications
4
58
0
2
Order By: Relevance
“…It was also shown that, without cooverexpression of Cdt1p, most of the overexpressed MCM subunits in yeast cell extracts formed sub-complexes other than the Mcm2-7p hexamer (Tsakraklides and Bell, 2010). These observations are consistent with our results that non-chromatinbound MCM proteins cannot form a heterohexameric complex after Cdt1p depletion in vivo.…”
Section: The Cdt1p-mcm6p Interaction Is Crucial For MCM Complex Formasupporting
confidence: 82%
See 1 more Smart Citation
“…It was also shown that, without cooverexpression of Cdt1p, most of the overexpressed MCM subunits in yeast cell extracts formed sub-complexes other than the Mcm2-7p hexamer (Tsakraklides and Bell, 2010). These observations are consistent with our results that non-chromatinbound MCM proteins cannot form a heterohexameric complex after Cdt1p depletion in vivo.…”
Section: The Cdt1p-mcm6p Interaction Is Crucial For MCM Complex Formasupporting
confidence: 82%
“…It was reported that approximately equimolar Cdt1p was readily co-purified with the Mcm2-7p complex from yeast cell extracts (Kawasaki et al, 2006;Remus et al, 2009;Tsakraklides and Bell, 2010). It was also shown that, without cooverexpression of Cdt1p, most of the overexpressed MCM subunits in yeast cell extracts formed sub-complexes other than the Mcm2-7p hexamer (Tsakraklides and Bell, 2010).…”
Section: The Cdt1p-mcm6p Interaction Is Crucial For MCM Complex Formamentioning
confidence: 94%
“…In vitro studies show that after loading, Mcm2 -7 no longer requires ORC, Cdc6, or Cdt1 to associate with origin DNA (Donovan et al 1997;Randell et al 2006). Consistent with this observation, in vitro studies show that the helicase loading proteins are released from the origin upon Mcm2 -7 loading (Randell et al 2006;Tsakraklides and Bell 2010). In contrast to these findings, in vivo inactivation of S. cerevisiae ORC or Cdc6 in late G 1 (after Mcm2 -7 loading) results in loss of Mcm2 -7originassociation(Aparicioetal.1997;Semple et al 2006;Chen et al 2007).…”
Section: Regulation and Dynamics Of Helicase Loadingsupporting
confidence: 65%
“…ORC ATP hydrolysis is also essential but functions after Cdc6 hydrolysis and appears to regulate repeated Mcm2 -7 loading (Bowers et al 2004;Randell et al 2006). One likely role for ORC ATP hydrolysis is to cause the release of the other helicase loading factors from the origin (Tsakraklides and Bell 2010). Evidence from studies of S. cerevisiae suggests that a second consequence of ATP hydrolysis is to disable ORC DNA binding until it is able to bind another molecule of ATP.…”
Section: Role Of Atp During Helicase Loadingmentioning
confidence: 99%
“…Chromatinbound ORC-Cdc6 function to recruit a Cdt1- heptamer to replication origins (Fig. 1A, step 2; Speck et al 2005;Randell et al 2006;Speck and Stillman 2007;Tsakraklides and Bell 2010;Evrin et al 2013;Frigola et al 2013;Sun et al 2013). Using an in vitro Mcm2-7 loading system that employs a purified ORC, Cdc6, Cdt1, and Mcm2-7 hexamer and an origin-containing plasmid, we recently observed formation of a loading intermediate termed OCCM in the presence of a slowly hydrolysable ATP analog, ATP-gS, which captured a complex containing ORC-Cdc6 bound to a single Mcm2-7 hexamer and one to two copies of Cdt1 (Takara and Bell 2011;Evrin et al 2013;Sun et al 2013).…”
mentioning
confidence: 99%